Analysis and Evaluation of Full System Simulators for Teaching Computer Architecture - Penna, Pedro H. M. M.; Freitas, Henrique C. (International Journal of Computer Architecture Education, 2013)
Teaching computer architecture in undergraduate computer science courses is fundamental. However, this task becomes a great challenge due to the rapid and continuous evolution of the field. In this context, different teaching methodologies emerge to facilitate student learning. One of them is the use of architecture simulators as a teaching tool. This article describes four full system simulators popular in academia, with the objective of analyzing and evaluating their characteristics for teaching. For this, the simulators are compared according to their characteristics, and one simulator is chosen to be used in the classroom and quantitatively evaluated through a questionnaire answered by students. The results reveal that students approve of the use of simulators as a teaching tool but face difficulties in understanding the simulator used due to the lack of documentation.